DIFFICULTIES EXPERIENCED TEACHERS AND STUDENTS IN LEARNING ENGLISH IN SEVENTH GRADE - Lala Zaelani; Silpia Rahayu (IKIP Siliwangi, 2024)
This research started from researchers observation on English students' ability that is still low at seventh-grade MTs Riyadhul Huda, and students' opinion of English is boring and difficult. Based on the problems, this research purpose was to analyze students' difficulties in understanding English learning, especially Reading Comprehension and Structure. The research method was descriptive qualitative. The research sampling was seventh-grade students at MTs Riyadhul Huda, in choosing the sample was used purposive sampling technique. This is done because the class has a lower average value than the other classes. More than 50% of students got a score under the Minimum Completeness criteria. To get the data, the researchers had done interviews for the students and English teacher, then done observation and document that were gotten the score of reading and structure material. From the resulting research was gotten that reading and structure understanding at seventh-grade students MTs Riyadhul Huda, low. 40% of 25 students were difficulties in understanding them. The difficulty of students in reading and understanding the structure is caused by the lack of concentration of students in studying, students' wrong study habits, and boredom of students in learning English, besides that the teacher rarely makes corrections to student assignments.